Analysis Of Local Wisdom Of The Mappadendang Tradition In The Perspective Of Islamic Education In Barru Regency - Suwarni Jayanti; Nurrahmah Nurahmah; Ma'rifah Ma'rifah; Alimuddin Alimuddin; Supriandi Supriandi (Journal of Indonesian Progressive Education, 2026)
The focus of the research includes the implementation of the Mappadendang tradition as the local wisdom of the community, the values of Islamic education contained in it, the analysis of the tradition from the perspective of Islamic Education, and its relevance to the learning of Islamic Religious Education. This study uses a descriptive qualitative method with a type of field research. Data was obtained through observation, interviews, and documentation involving traditional leaders, religious leaders, village governments, traditional actors, and communities involved in the implementation of Mappadendang. Data analysis was carried out using the Miles, Huberman, and Saldaña model which included data condensation, data presentation, and conclusion drawn. The results of the study show that the Mappadendang tradition is still preserved by the people of Barru Regency as a form of expression of gratitude for the harvest as well as a means of strengthening the community's social relations. This tradition contains Islamic educational values which include the value of gratitude, Islamic ukhuwah, mutual cooperation, cooperation, responsibility, and noble morals. From the perspective of Islamic Education, the Mappadendang tradition is acceptable as long as it does not contradict the aqidah and sharia of Islam. This tradition has a strong relevance to Islamic Religious Education because it can be used as a source of learning based on local wisdom that supports the formation of students' character. Therefore, the Mappadendang tradition not only functions as a cultural heritage, but also as an educational medium that integrates local cultural values with Islamic teachings in people's lives.